Photosynthetic Carbon Assimilation and Electron Transport Rates in Two Symbiont-Bearing Planktonic Foraminifera - Takagi, Haruka; Kimoto, Katsunori; Fujiki, Tetsuichi (Frontiers in Marine Science, 2022)
Photosymbiosis is one of the key features characterizing planktonic foraminifera; the number of symbiont cells within a single host has been reported to be well over thousands, meaning that photosynthesis by photosymbiosis may be a “hot spot” for primary production, especially in oligotrophic oceans. As microenvironmental conditions around foraminifera are greatly affected by rapid biological activities—such as photosynthesis and respiration—information on the photosynthetic activities of symbionts is essential to interpret the geochemical proxies recorded in foraminiferal tests (e.g., δ13C and δ18O). Recently, active chlorophyll fluorometry has been increasingly employed as a useful tool for immediate estimation of photosynthesis. However, carbon assimilation rates are the only direct indicator of the photosynthetic carbon flux. Therefore, before utilizing active fluorescence methods to understand carbon dynamics in foraminiferal symbiosis, it is necessary to confirm the relationship between the fluorescence-based photosynthetic rate [electron transport rate (ETR)] and carbon assimilation rate (P). Here, these two rates were compared for two species, Trilobatus sacculifer and Globigerinella siphonifera Type II, using 14C-tracer experiments and active fluorometric measurements by fast repetition rate fluorometry. The results showed a significant positive correlation between the P and ETR of the two species, indicating that carbon assimilation can be estimated by the fluorometric method. However, the regression slopes, which represent the apparent electron requirement for carbon assimilation (e–/C), were significantly different in the two species, and were estimated at 26.2 for T. sacculifer and 96.5 for G. siphonifera. These are strikingly high, considering the theoretically and empirically realistic e–/C values. We hypothesized that the high e–/C observed may be due in part to the use of unlabeled respiratory carbon (underestimation of P). A simple mass balance calculation suggests that a significant amount of carbon should derive from the host’s respired CO2, whose contribution is higher in G. siphonifera than in T. sacculifer. Within the context of using test geochemical parameters, such as δ13C, as paleoceanographic proxies, it is important to note that the potential magnitude of the photosynthetic effect varies among species. This attempt to couple ETR and P could comprehensively reveal an interesting perspective on the intimate interactions existing within photosymbiotic systems.